Early pregnancy diagnosis in cattle and buffaloes from milk - LAKHCHAURA, B D; CHAVAN, SEEMA; UMAPATHI, V (The Indian Journal of Animal Reproduction, 2023)
An immunodiagnostic kit has been developed for the early pregnancy diagnosis in cattle and buffaloes, based on thedetection of progestrerone in the milk by dipstick EIA method. Discriminatory level was placed at 5-ng/ml progesterone forpregnant animals and I ng/lml for non-pregnant animals. The accuracy for positive diagnosis was 90-92% while non-pregnancy wasdiagnosed with 100°/c, accuracy. The pregnancy can be diagnosed between 18-24 days of post insemination by this method. All thecomponents in the kits are supplied in lyophilized form for a prolonged shelf-life and convenience for field application. Assay is wellsuited for routine testing particulariy in cattle and buffaloes since milk sampling is easy and doesn't disturb the animal.
Keywords: Pregnancy diagnosis; enzyme immunoassay; cattle; buffalo